Graphene modified nickel foam matrix growth copper-based composite catalyst and preparation method
The copper -based complex catalyst is used to modify the nickel nickel matrix in situ through graphene, which solves the problem of toxic organic pollutants emitted by the printing and dyeing industrial emissions in the existing technology, and realizes high -efficiency catalytic reduction of aromatherapy nitrite and degradation of pineral nitrogen. The effect of dyes and improves the practicality and long -term stability of the catalyst.
Patent Information
- Application Number
- CN202110288861.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-03-18
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2041-03-18
AI Technical Summary
The prior art is difficult to effectively degrade toxic organic pollutants such as p-nitrophenol (4-NP) emitted by the printing and dyeing industry, and the high cost and complex synthesis conditions of precious metal-based catalysts limit their practical application.
Use graphene to modify the nickel nickel matrix to grow copper-based complex catalysts in situ. Nano -array type copper -based complex/RGO/foam nickel catalyst.
This catalyst shows excellent catalytic restoration of aromatic nitride and degradation of pineral dye dyes, and it is easy to separate and recycle and reuse. Promotion and long -term stability.
Smart Images

Figure CN113019376B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmental catalysis, and in particular provides a graphene-modified nickel foam matrix in-situ grown copper-based composite catalyst and a preparation method thereof. The catalyst can be effectively used for catalytic reduction of aromatic nitro compounds and degradation of anionic azo dyes. Technical Background
[0002] Nitrophenol and its derivatives are one of the most difficult organic pollutants to treat in wastewater discharged from the printing and dyeing industry. Among them, p-nitrophenol (4-NP) is particularly toxic, anthropogenic and carcinogenic, and is difficult to degrade and easy to accumulate. In order to effectively degrade 4-NP, researchers have developed a variety of physical and chemical methods. Among them, one of the most commonly used and efficient methods is the catalytic reduction process of metal-based catalysts using sodium borohydride (NaBH4) as a reducing agent. Among them, precious metal-based catalysts usually have high activity, but their large-scale practical application is limited by high cost, low abundance and complex and cumbersome synthesis conditions. Therefore, the development of new and efficient non-precious metal-based transition metal catalysts for catalytic reduction of 4-NP is an important research direction.
[0003] Layered Double Hydroxide (LDH) is a layered compound composed of positively charged layers and interlayer anions in an orderly manner. It has been widely studied due to its advantages such as adjustable layer composition and high atomic-level dispersion of elements. However, due to strong inter-particle interactions, single two-dimensional nanosheets of hydrotalcite prepared by traditional coprecipitation methods are very easy to aggregate. Hybridizing LDH with graphene, which has a high specific surface area, good conductivity, and high chemical and thermal stability, can effectively improve the dispersion of two-dimensional nanosheets. For example, Zhang et al. (Chinese invention patent: CN 104857960 A) used a one-step liquid phase coprecipitation method modified with citric acid to prepare a powdery multi-level structure LDHs nanosheet array / graphene hybrid material, and the three-dimensional nanosheet array composite oxide catalyst obtained by calcination showed excellent activity in the removal of nitrogen oxides and soot combustion reactions.
[0004] However, powder catalysts have the disadvantages of easy aggregation, difficult recovery and partial loss during the reaction process. Therefore, they can be compounded with rigid matrix nickel foam, which is extremely beneficial to improve the stability of the composite and further promote the exposure of active components. In addition, nickel foam matrix catalysts also have the advantages of simple operation, easy separation, recovery and reuse. Therefore, the design first adopts citric acid-assisted hydrothermal treatment to obtain graphene oxide-modified nickel foam matrix, and then uses a simple and green citric acid-assisted liquid phase coprecipitation-hydrothermal method to in situ grow copper-based hydrotalcite on the graphene oxide-modified nickel foam matrix to obtain a new type of copper-based hydrotalcite / rGO / nickel foam hybrid, denoted as M 2+ M3+ -LDH / rGO / NF,M 2+ and M 3+ are divalent and trivalent metal ions, respectively; after moderate calcination in nitrogen atmosphere, a nanosheet array-like copper-based composite / rGO / nickel foam catalyst was obtained, denoted as Cu@Cu2O-M 2+ M 3+ (O) / rGO / NF. In the current research, the in-situ growth of hierarchical structure copper-based composite catalysts on reduced graphene oxide modified nickel foam matrix synthesized by this method has not been reported, and the application of nickel foam matrix supported catalysts in the catalytic reduction of organic water pollutants has rarely been reported. Summary of the invention
[0005] The purpose of the present invention is to provide a graphene-modified nickel foam matrix in-situ grown copper-based composite catalyst and a preparation method thereof, wherein the synthesis process is simple and green, and the operating conditions of high temperature and high pressure and the use of organic reagents are avoided. The obtained catalyst exhibits excellent catalytic reduction of aromatic nitro compounds and degradation of anionic azo dyes, and is easy to separate, recycle and reuse, effectively avoiding the disadvantages of powder catalysts being easy to aggregate, difficult to recycle and partially lost during the reaction process, thereby improving the practicality and long-term stability of the catalyst.
[0006] The catalyst of the present invention is a multi-level structure copper-based hydrotalcite / rGO / foam nickel hybrid M 2+ M 3+ -LDH / rGO / NF, hydrotalcite nanosheets grow vertically and staggered on the surface of nickel foam matrix uniformly coated with reduced graphene oxide, forming a three-dimensional "honeycomb" nanosheet array morphology; the copper-based composite catalyst Cu@Cu2O-M was moderately calcined in a nitrogen atmosphere. 2+ M 3+ (O) / rGO / NF well maintains the nanosheet array morphology, in which the composite nanosheet M 2+ M 3+ (O) The size is 50-150 nm, the thickness is 4-15 nm, and the size of the core-shell active Cu@Cu2O nanoparticles generated by in situ self-reduction is 8-40 nm, which are uniformly and highly dispersed at the junction of adjacent composite nanosheets and rGO / nickel foam matrix.
[0007] The catalyst of the present invention is prepared by firstly using citric acid assisted hydrothermal treatment to obtain a nickel foam matrix uniformly coated with graphene oxide, and then in situ growing copper-based hydrotalcite on the nickel foam matrix modified with graphene oxide by citric acid assisted liquid phase coprecipitation-hydrothermal method to obtain a novel copper-based hydrotalcite / rGO / nickel foam hybrid M 2+ M 3+-LDH / rGO / NF; after calcination in nitrogen atmosphere, a nanosheet array-like copper-based composite / rGO / foam nickel catalyst Cu@Cu2O-M was obtained. 2+ M 3+ (O) / rGO / NF. Specifically comprising the following steps:
[0008] (1) ultrasonically cleaning the nickel foam with acetone, 2M hydrochloric acid solution, deionized water and anhydrous ethanol for 15 minutes each, and then vacuum drying at 75-85° C. for 170-180 minutes;
[0009] (2) 523 mesh natural flake graphite was chemically oxidized to obtain graphite oxide gel using the improved Hummers method;
[0010] (3) The graphite oxide gel (GO, 10 mg / mL) prepared in step (2) and deionized water were ultrasonically dispersed for 15 to 25 minutes to obtain a completely exfoliated graphite oxide suspension (60 mL in total), citric acid (CA) was added and ultrasonicated for 5 to 10 minutes to obtain a uniform and stable CA-modified GO suspension (CA-GO), which was transferred to a 100 mL polytetrafluoroethylene-lined autoclave; then two 3 cm × 5 cm pretreated clean nickel foam (NF) sheets were completely immersed in the CA-GO suspension, the NF sheets needed to be slightly bent and inserted vertically into the reactor with the longer side of 5 cm, and hydrothermally reacted at 90 to 150° C. for 4 to 8 hours. After the reaction was completed, the product was naturally cooled to room temperature, and the obtained product was repeatedly rinsed with deionized water and ultrasonically washed for 0.5 to 1 minute, and freeze-dried for 5 to 8 hours to obtain a nickel foam matrix GO / NF uniformly coated with graphene oxide;
[0011] (4) Cut the two 3 cm × 5 cm GO / NF matrices obtained in step (3) into eight 1.5 cm × 2.5 cm small pieces, place them in a four-necked flask containing 120 mL of deionized water, add 5-30 mg of citric acid, and add the mixed alkali solution dropwise under continuous stirring. When the solution pH = 10 ± 0.1, stop adding the alkali solution. After stabilization for 5-10 minutes, add 100 mL of the mixed salt and mixed alkali solution dropwise at the same time to keep the solution pH stable at 10 ± 0.1. After the mixed salt solution was added, the obtained slurry containing the rGO / NF matrix was transferred to a polytetrafluoroethylene-lined reactor. Two pieces of 1.5 cm×2.5 cm rGO / NF matrix and 75 mL of the above slurry were placed in each 100 mL reactor, and then crystallized at 80-120°C for 4-8 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5-8 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid precursor, which was recorded as M 2+ M 3+ -LDH / rGO / NF,M 2+and M 3+ They are divalent and trivalent metal ions respectively;
[0012] (5) The product obtained in step (4) was placed in a flowing N2 of 50 to 200 mL / min, maintained at 380 to 600°C for 2 to 4 hours at a heating rate of 1 to 5°C / min, and then naturally cooled to room temperature to obtain a nanosheet array-type copper-based composite / rGO / nickel foam catalyst, denoted as Cu@Cu2O-M 2+ M 3+ (O) / rGO / NF.
[0013] Preferably, in the above technical solution, the concentration range of the graphite oxide suspension described in step (3) is 0.5-3 mg / mL; the mass ratio of graphite oxide to citric acid is 2:1, and the ultrasonic power is 300W.
[0014] Preferably, in the above technical solution, the mixed alkali in step (4) comprises NaOH and Na2CO3, and [CO3 2- ] / [M 3+ ]=2,[OH - ] / [CO3 2- ]=3.2.
[0015] Preferably, in the above technical solution, the mixed salt described in step (4) includes divalent and trivalent metal salts, which exist in the form of nitrate or acetate or a mixed form thereof, and the total molar number of the metal salt is 5 to 20 mmol. 2+ Cu 2+ Cu 2+ with Ni 2+ 、Co 2+ , Mn 2+ and Mg 2+ When M 2+ Cu 2+ When the trivalent metal ion M 3+ Fe 3+ and Al 3+ One or a combination of two of the above, with a molar ratio of M 2+ / M 3+ The value is 1.5~2, when M 3+ Fe 3+ and Al 3+ When the molar ratio of Fe 3+ / Al 3+ The value is 1 / 9~1; when M 2+ Cu 2+ with Ni 2+ 、Co 2+ , Mn 2+ and Mg 2+When one of the 3+ Only Al 3+ , molar ratio M 2 + / M 3+ The value is 3 / 1, then Cu 2+ The molar number is 0.625~10mmol.
[0016] Compared with the prior art, the present invention has the following characteristics and advantages:
[0017] (1) The present invention uses loose and porous nickel foam as a matrix, and uses citric acid-modified hydrothermal treatment to uniformly and firmly coat graphene oxide on the surface of the nickel foam matrix. The citric acid-assisted liquid phase coprecipitation-hydrothermal method and subsequent nitrogen atmosphere calcination treatment are further used to prepare a nanosheet array-type copper-based composite / rGO / nickel foam catalyst Cu@Cu2O-M 2+ M 3+ (O) / rGO / NF. Among them, the composite M 2+ M 3+ (O) The nanosheets grow vertically and staggered on the surface of the rGO / NF matrix, and the core-shell Cu@Cu2O nanoparticles generated by in-situ self-reduction are evenly distributed at the junction of adjacent composite nanosheets and the rGO / NF matrix. The synthesis process of the present invention is simple and green, with mild conditions, avoiding high temperature and high pressure conditions and the use of organic reagents, and is easy to operate.
[0018] (2) The multi-level structure composite catalyst Cu@Cu2O-M obtained by the present invention 2+ M 3+ (O) / rGO / NF exhibits excellent catalytic reduction of aromatic nitro compounds and degradation of anionic azo dyes. Among them, aromatic nitro compounds include p-nitrophenol, o-nitrophenol, m-nitrophenol, 2,4-dinitrotoluene, 4-nitrobenzaldehyde and 4-nitroaniline; organic dyes include methyl orange, acid orange 7, rhodamine B and methylene blue. In addition, the obtained matrix-type catalyst is easy to separate, recycle and reuse, which effectively avoids the shortcomings of powder catalysts such as easy aggregation, difficult recovery and partial loss during the reaction process, and improves the practicality and long-term stability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is the scanning electron microscope image of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1 (scale is 10μm).
[0020] Figure 2 This is the scanning electron microscope image of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1 (scale is 200 nm).
[0021] Figure 3 This is the scanning electron microscope image of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1 (scale is 100 nm).
[0022] Figure 4 This is the X-ray diffraction pattern of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1.
[0023] Figure 5 This is the UV-visible spectrum of the catalytic reduction of p-nitrophenol by 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1. DETAILED DESCRIPTION
[0024] The present invention is further described in detail below in conjunction with examples, but the embodiments of the present invention are not limited thereto.
[0025] Example 1
[0026] (1) Two pieces of nickel foam with a size of 3 cm × 5 cm were ultrasonically cleaned with acetone, 2 M hydrochloric acid solution, deionized water and anhydrous ethanol for 15 minutes each, and then vacuum dried at 80° C. for 3 hours;
[0027] (2) 523 mesh natural flake graphite was chemically oxidized by the improved Hummers method to obtain graphite oxide gel; 60 mg of graphite oxide gel (10 mg / mL, 6 mL) and 54 mL of deionized water were ultrasonically dispersed for 20 minutes to obtain a completely exfoliated graphite oxide suspension, and then 30 mg of citric acid was added and ultrasonicated for 10 minutes to obtain a uniform and stable citric acid-modified graphene oxide suspension;
[0028] (3) The suspension obtained in step (2) was transferred to a 100 mL polytetrafluoroethylene-lined autoclave; the pretreated nickel foam obtained in step (1) was then completely immersed in the citric acid-modified graphene oxide suspension, the nickel foam sheet was slightly bent, and the longer side of 5 cm was vertically inserted into the reactor, and the reaction was carried out at 120° C. for 5 hours. After the reaction was completed, the reaction was naturally cooled to room temperature, and the obtained product was repeatedly rinsed with deionized water and ultrasonically washed for 0.5 minutes, and freeze-dried for 5 hours to obtain a nickel foam matrix GO / NF uniformly coated with graphene oxide;
[0029] (4) 3.75 mmol Cu(NO3)2·3H2O, 3.75 mmol Ni(NO3)2·6H2O and 2.5 mmol Al(NO3)3·9H2O were dissolved in 100 mL of deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 7.5 mmol Na2CO3 and 24 mmol NaOH were dissolved in 150 mL of deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution;
[0030] (5) The GO / NF matrix obtained in step (3) was cut into 8 small pieces of 1.5 cm×2.5 cm, placed in a four-necked flask containing 120 mL of deionized water, and 10 mg of citric acid was added. Under continuous stirring, the mixed alkaline solution described in step (4) was added dropwise. When the pH value of the solution was 10±0.1, the addition of the alkaline solution was stopped. After stabilization for 10 minutes, the mixed salt and the mixed alkaline solution were added dropwise at the same time to keep the pH value of the solution stable at 10±0.1. After the addition of the mixed salt solution was completed, the obtained slurry containing the rGO / NF matrix was transferred to a polytetrafluoroethylene-lined reactor. Two pieces of 1.5 cm×2.5 cm rGO / NF matrix and 75 mL of the above slurry were placed in each 100 mL reactor, and then crystallized at 90°C for 6 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5 hours to obtain a nanosheet array-type copper-based hydrotalcite / rGO / foam nickel hybrid, denoted as Cu 1.5 Ni 1.5 Al-LDH / rGO / NF-1;
[0031] (6) The product obtained in step (5) was calcined at 380° C. for 4 hours in a nitrogen flow of 50 mL / min with a heating rate of 1° C. / min to obtain a multi-level structured nanosheet array-type copper-based composite / rGO / nickel foam catalyst, recorded as 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1.
[0032] The scanning electron microscopy image of the composite catalyst 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 is shown in Figure 1-3 The catalyst is composed of CuNiAl(O) composite nanosheets with a size of ~78nm×8nm vertically staggered on the surface of the rGO / NF matrix, showing a nanosheet array morphology. The X-ray diffraction pattern of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 is shown in Figure 2The diffraction peaks at about 43° (111), 50° (200) and 75° (220) and the peaks at 37° (111), 42° (200) and 62° (220) can correspond to standard cards Cu (standard card number 04-0836) and Cu2O (standard card number 78-2076), respectively, and the peak at about 63° belongs to NiO (220) (standard card number 73-1519).
[0033] The catalytic reduction performance of the above-obtained 1.5Cu@Cu2O-NiAl(O) / rGO / NF-1 was tested:
[0034] The catalytic hydrogenation of 4-NP was used as a model reaction to evaluate the catalytic activity of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1. The specific operation was as follows: 200μL of 1mM 4-NP solution and 2.5mL of 10mM freshly prepared NaBH4 solution were added to a standard quartz cuvette in sequence, 1cm×0.5cm of 1.5Cu@Cu2O-NiAl(O) / rGO / NF-1 catalyst was cut and placed in the above mixed solution and the timing was started. The catalyst was taken out every 0.5 minutes and the UV-vis absorption spectrum was recorded (scanning range 250~500nm). The absorbance at 400nm was recorded over time and is shown in Figure 3 . The results show that 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 can rapidly catalyze the reduction of 4-NP in 1 minute, indicating that 1.5Cu@Cu2O-NiAl(O) / rGO / NF-1 prepared in Example 1 has excellent catalytic reduction activity for 4-NP. The same test steps were used to evaluate the activity of the catalyst in catalytic reduction of other aromatic nitro compounds and degradation of organic dyes. Among them, other aromatic nitro compounds include o-nitrophenol, m-nitrophenol, 2,4-dinitrotoluene, 4-nitrobenzaldehyde and 4-nitroaniline; organic dyes include methyl orange, acid orange 7, rhodamine B and methylene blue. All the above experimental operations were carried out at room temperature 25°C.
[0035] The cyclic stability test of 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 was carried out according to the following steps: The first cycle reaction was consistent with the above-mentioned activity test process. Starting from the second cycle, the catalyst was taken out in each cycle, washed once with deionized water, and directly placed in a new 4-NP and NaBH4 mixed solution used in the performance test. The rest of the operations remained unchanged, and a total of 30 cycles were performed. The results showed that the reaction time did not increase significantly when the cycle reached the 30th cycle, indicating that the 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-1 prepared in Example 1 has very excellent cyclic stability.
[0036] Example 2
[0037] This embodiment is the same as Embodiment 1 except for the following features: 30 mg of graphite oxide gel (10 mg / mL, 3 mL) and 57 mL of deionized water are ultrasonically dispersed for 15 minutes to obtain a completely exfoliated graphite oxide suspension, 15 mg of citric acid is added and ultrasonication is continued for 5 minutes to obtain a uniform and stable citric acid-modified graphene oxide suspension; the above suspension is transferred to a 100 mL polytetrafluoroethylene-lined autoclave; then the pretreated nickel foam obtained in step (1) of Embodiment 1 is completely immersed in the citric acid-modified graphene oxide suspension, the NF sheet needs to be slightly bent and vertically inserted into the reactor with the longer side of 5 cm, and hydrothermally reacted at 90° C. for 8 hours. After the reaction is completed, it is naturally cooled to room temperature, the resulting product is repeatedly rinsed with deionized water and ultrasonically washed for 1 minute, and freeze-dried for 5 hours to obtain a nickel foam matrix GO / NF uniformly coated with graphene oxide; the subsequent steps are the same as in Embodiment 1 to obtain the catalyst 1.5Cu@Cu2O-CuNiAl(O) / rGO / NF-2.
[0038] Example 3
[0039] This embodiment is the same as the embodiment 1 except for the following features: 180 mg of graphite oxide gel (10 mg / mL, 18 mL) and 42 mL of deionized water are ultrasonically dispersed for 25 minutes to obtain a completely exfoliated graphite oxide suspension, 90 mg of citric acid is added and ultrasonication is continued for 10 minutes to obtain a uniform and stable citric acid-modified graphene oxide suspension; the above suspension is transferred to a 100 mL polytetrafluoroethylene-lined autoclave; then the pretreated nickel foam obtained in step (1) of embodiment 1 is completely immersed in the citric acid-modified graphene suspension, the NF sheet needs to be slightly bent and vertically inserted into the reactor with the longer side of 5 cm, and hydrothermally reacted at 150° C. for 4 hours. After the reaction is completed, it is naturally cooled to room temperature, the resulting product is repeatedly rinsed with deionized water and ultrasonically washed for 1 minute, and freeze-dried for 5 hours to obtain a nickel foam matrix GO / NF uniformly coated with graphene oxide; the subsequent steps are the same as in embodiment 1 to obtain the catalyst 1.5Cu@Cu2O-NiAl(O) / rGO / NF-3.
[0040] Example 4
[0041] This embodiment is the same as embodiment 1 except for the following features: 0.625mmol Cu(NO3)2·3H2O, 3.125mmol Ni(NO3)2·6H2O and 1.25mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 3.75mmol Na2CO3 and 12mmol NaOH are dissolved in 150mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of embodiment 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 5mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 5 minutes, the mixed salt and mixed alkali solutions are added dropwise at the same time to keep the solution pH value constant. After the mixed salt solution was added, the slurry containing GO / NF was transferred to a polytetrafluoroethylene-lined reactor. Two 1.5 cm × 2.5 cm GO / NF matrices and 75 mL of the slurry were placed in each 100 mL reactor. The mixture was crystallized at 80 ° C for 8 hours. After the reaction was completed, the reaction was naturally cooled to room temperature. The product was repeatedly washed with deionized water and freeze-dried for 8 hours to obtain a nanosheet array-type copper-based hydrotalcite / rGO / foam nickel hybrid, which was recorded as Cu 0.5 Ni 2.5 Al-LDH / rGO / NF, the obtained product was calcined at 500°C for 3 hours in a nitrogen flow of 200 mL / min, with a heating rate of 4°C / min to obtain a nanosheet array-type copper-based composite / rGO / foam nickel catalyst, recorded as 0.5Cu@Cu2O-CuNiAl(O) / rGO / NF.
[0042] Example 5
[0043] This example is the same as Example 1 except for the following features: 10 mmol Cu(NO3)2·3H2O, 5 mmol Ni(NO3)2·6H2O and 5 mmol Al(NO3)3·9H2O are dissolved in 100 mL of deionized water and ultrasonically treated for 5 minutes to obtain a mixed salt solution; 15 mmol Na2CO3 and 48 mmol NaOH was dissolved in 150 mL of deionized water and ultrasonically treated for 5 minutes to obtain a mixed alkaline solution. The GO / NF matrix obtained in step (3) of Example 1 was cut into 8 small pieces of 1.5 cm × 2.5 cm, placed in a four-necked flask containing 120 mL of deionized water, and 20 mg of citric acid was added. Under continuous stirring, the mixed alkaline solution was added dropwise. When the pH of the solution was 10 ± 0.1, the addition of the alkaline solution was stopped. After stabilization for 10 minutes, the mixed salt and the mixed alkaline solution were added dropwise at the same time to keep the pH value of the solution stable at 10 ± 0.1. After the addition of the mixed salt solution was completed, the obtained slurry containing the rGO / NF matrix was transferred to a polytetrafluoroethylene-lined reactor. Two pieces of 1.5 cm × 2.5 cm rGO / NF matrix and 75 mL of the above slurry were placed in a 100 mL reactor and crystallized at 120 ° C for 4 hours. After the reaction was completed, it was naturally cooled to room temperature. The resulting product was repeatedly washed with deionized water and freeze-dried for 6 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, recorded as Cu2Ni1Al-LDH / rGO / NF; the resulting product was calcined at 600 ° C for 2 hours in a nitrogen flow of 100 mL / min, with a heating rate of 5 ° C / min, to obtain a nanosheet array-type copper-based composite / rGO / foam nickel catalyst, recorded as 2.0Cu@Cu2O-CuNiAl(O) / rGO / NF.
[0044] Example 6
[0045] This example is the same as Example 1 except for the following features: 3.75mmol Cu(NO3)2·3H2O, 3.75mmol Co(NO3)2·6H2O and 2.5mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 7.5mmol Na2CO3 and 24mmol NaOH are dissolved in 150mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of Example 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 20mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed salt and mixed alkali solution are added dropwise at the same time to maintain the solution pH at 10±0.1. The H value has been stable at 10±0.1. After the mixed salt solution is added, the obtained slurry containing rGO / NF matrix is transferred to a polytetrafluoroethylene-lined reactor. Two pieces of 1.5 cm×2.5 cm rGO / NF matrix and 75 mL of the above slurry are placed in each 100 mL reactor. Crystallization is carried out at 90°C for 6 hours. After the reaction is completed, it is naturally cooled to room temperature. The obtained product is repeatedly washed with deionized water and freeze-dried for 5 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which is recorded as Cu 1.5 Co 1.5 Al-LDH / rGO / NF, the subsequent calcination steps are the same as in Example 1, and a nanosheet array-type copper-based composite / rGO / foam nickel catalyst is obtained, which is recorded as 1.5Cu@Cu2O-CuCoAl(O) / rGO / NF.
[0046] Example 7
[0047] This example is the same as Example 1 except for the following features: 3.75mmol Cu(NO3)2·3H2O, 3.75mmol Mn(NO3)2·6H2O and 2.5mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 7.5mmol Na2CO3 and 24mmol NaOH are dissolved in 150mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of Example 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 15mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed alkali and mixed salt solutions are added dropwise at the same time to maintain the solution pH at 10±0.1. The H value has been stable at 10±0.1; after the mixed salt solution is added dropwise, the obtained slurry containing rGO / NF matrix is transferred to a polytetrafluoroethylene-lined reactor, and 2 pieces of 1.5 cm×2.5 cm rGO / NF matrix and 75 mL of the above slurry are placed in each 100 mL reactor, and crystallized at 90°C for 6 hours. After the reaction is completed, it is naturally cooled to room temperature, and the obtained product is repeatedly washed with deionized water and freeze-dried for 3 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which is recorded as Cu 1.5 Mn 1.5 Al-LDH / rGO / NF, the subsequent calcination steps are the same as in Example 1, and a nanosheet array-type copper-based composite / rGO / foam nickel catalyst is obtained, which is recorded as 1.5Cu@Cu2O-CuMnAl(O) / rGO / NF.
[0048] Example 8
[0049] This embodiment is the same as embodiment 1 except for the following features: 3.75mmol Cu(NO3)2·3H2O, 3.75mmol Mg(NO3)2·6H2O and 2.5mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 7.5mmol Na2CO3 and 24mmol NaOH are dissolved in 150mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of embodiment 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 10mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed alkali and mixed salt solutions are added dropwise at the same time to maintain the solution pH at 10±0.1. The H value has been stable at 10±0.1; after the mixed salt solution is added dropwise, the obtained slurry containing rGO / NF matrix is transferred to a polytetrafluoroethylene-lined reactor, and 2 pieces of 1.5 cm×2.5 cm rGO / NF matrix and 75 mL of the above slurry are placed in each 100 mL reactor, and crystallized at 90°C for 6 hours. After the reaction is completed, it is naturally cooled to room temperature, and the obtained product is repeatedly washed with deionized water and freeze-dried for 6 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which is recorded as Cu 1.5 Mg 1.5 Al-LDH / rGO / NF, the subsequent calcination steps are the same as in Example 1, and a nanosheet array-type copper-based composite / rGO / foam nickel catalyst is obtained, which is recorded as 1.5Cu@Cu2O-CuMgAl(O) / rGO / NF.
[0050] Example 9
[0051] This embodiment is the same as embodiment 1 except for the following features: 6.67mmol Cu(NO3)2·3H2O, 1.67mmol Fe(NO3)3·9H2O and 1.67mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water, and ultrasonically treated for 5 minutes to obtain a mixed salt solution; 10.02mmol Na2CO3 and 32.06mmol NaOH are dissolved in 150mL deionized water, and ultrasonically treated for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of embodiment 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 10mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed alkali and mixed salt solutions are added dropwise at the same time to keep the solution The pH value was kept stable at 10±0.1. After the addition of the mixed salt solution was completed, the obtained slurry containing GO / NF was transferred to a polytetrafluoroethylene-lined reactor. Two 1.5 cm×2.5 cm GO / NF matrices and 75 mL of the above slurry were placed in each 100 mL reactor. The mixture was crystallized at 90°C for 6 hours. After the reaction was completed, the mixture was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which was recorded as Cu2Fe 0.5 Al 0.5 -LDH / rGO / NF, the subsequent calcination steps were the same as in Example 1, and a nanosheet array-type copper-based composite / rGO / foam nickel catalyst was obtained, which was recorded as 2.0Cu@Cu2O-CuFeAl(O) / rGO / NF.
[0052] Example 10
[0053] This embodiment is the same as embodiment 1 except for the following features: 6.0mmol Cu(NO3)2·3H2O, 0.4mmol Fe(NO3)3·9H2O and 3.6mmol Al(NO3)3·9H2O are dissolved in 100mL deionized water, and ultrasonically treated for 5 minutes to obtain a mixed salt solution; 12mmol Na2CO3 and 38.4mmol NaOH are dissolved in 150mL deionized water, and ultrasonically treated for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of embodiment 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask filled with 120mL deionized water, 20mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the solution pH=10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed alkali and mixed salt solutions are added dropwise at the same time to keep the solution at 40℃. The pH value of the solution was kept stable at 10±0.1. After the mixed salt solution was added dropwise, the obtained slurry containing GO / NF was transferred to a polytetrafluoroethylene-lined reactor. Two 1.5 cm×2.5 cm GO / NF matrices and 75 mL of the above slurry were placed in each 100 mL reactor. The mixture was crystallized at 90°C for 6 hours. After the reaction was completed, the mixture was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which was recorded as Cu 1.5 Fe 0.1 Al 0.9 -LDH / rGO / NF, the subsequent calcination steps were the same as in Example 1, and a nanosheet array-type copper-based composite / rGO / nickel foam catalyst was obtained, which was recorded as 1.5Cu@Cu2O-CuFeAl(O) / rGO / NF.
[0054] Embodiment 11
[0055] This embodiment is the same as embodiment 1 except for the following features: 13.33mmol Cu(NO3)2·3H2O and 6.67mmol Al(NO3)2·9H2O are dissolved in 100mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed salt solution; 20.0mmol Na2CO3 and 64.0mmol NaOH are dissolved in 150mL deionized water and subjected to ultrasonic treatment for 5 minutes to obtain a mixed alkali solution; the GO / NF matrix obtained in step (3) of embodiment 1 is cut into 8 small pieces of 1.5cm×2.5cm, placed in a four-necked flask containing 120mL deionized water, 10mg citric acid is added, and the mixed alkali solution is added dropwise under continuous stirring. When the pH value of the solution is 10±0.1, the addition of the alkali solution is stopped. After stabilization for 10 minutes, the mixed alkali and mixed salt solutions are added dropwise at the same time to keep the pH value of the solution stable at 10±0.1; after the addition of the mixed salt solution is completed, the obtained slurry containing rGO / NF matrix is The slurry was transferred to a polytetrafluoroethylene-lined reactor, and 2 pieces of 1.5 cm × 2.5 cm rGO / NF matrix and 75 mL of the above slurry were placed in each 100 mL reactor. The reaction was crystallized at 90 ° C for 6 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid, which was recorded as Cu2Al-LDH / rGO / NF. The subsequent calcination steps were the same as those in Example 1 to obtain a nanosheet array-type copper-based composite / rGO / foam nickel catalyst, which was recorded as 2.0Cu@Cu2O-CuAl(O) / rGO / NF.
Claims
1. A graphene-modified nickel foam matrix grown copper-based composite catalyst, characterized in that: In the hierarchical structured copper-based hydrotalcite / rGO / nickel foam hybrid, hydrotalcite nanosheets grow vertically and staggered on the surface of the nickel foam matrix uniformly coated with rGO, forming a three-dimensional "honeycomb" nanosheet array morphology; after calcination in a nitrogen atmosphere, a nanosheet array-type copper-based composite / rGO / nickel foam catalyst was obtained, in which the composite nanosheets were 50-150nm in size and 4-15nm in thickness, and the core-shell Cu@Cu2O nanoparticles generated by in-situ self-reduction were 8-40nm in size and uniformly distributed at the junction of adjacent composite nanosheets and rGO / nickel foam matrix.
2. A method for preparing a copper-based composite catalyst grown on a graphene-modified nickel foam matrix according to claim 1, characterized in that: The following steps are involved: (1) ultrasonically cleaning the nickel foam with acetone, 2M hydrochloric acid solution, deionized water and anhydrous ethanol for 15 minutes each, and then vacuum drying at 75-85° C. for 170-180 minutes; (2) 523 mesh natural flake graphite was chemically oxidized to obtain graphite oxide gel using the improved Hummers method; (3) ultrasonically dispersing the 10 mg / mL graphite oxide gel (GO) prefabricated in step (2) and deionized water for 15 to 25 minutes to obtain a completely exfoliated graphite oxide suspension, with a total of 60 mL of graphite oxide suspension, and then adding citric acid and continuing ultrasonication for 5 to 10 minutes to obtain a uniform and stable citric acid-modified graphite oxide suspension, which is transferred to a 100 mL polytetrafluoroethylene-lined autoclave; then completely immersing two 3 cm×5 cm pretreated clean nickel foam (NF) sheets in the citric acid-modified graphite oxide suspension, slightly bending the NF sheet and vertically inserting it into the autoclave with the longer side of 5 cm, hydrothermally treating it at 90 to 150° C. for 4 to 8 hours, cooling it naturally to room temperature after the reaction is completed, repeatedly rinsing the resulting product with deionized water and ultrasonically washing it for 0.5 to 1 minute, and freeze-drying it for 5 to 8 hours to obtain a nickel foam matrix GO / NF uniformly coated with graphene oxide; (4) Put the two pieces of 3cm×5cm obtained in step (3) The GO / NF matrix was cut into 8 pieces of 1.5 cm × 2.5 cm, placed in a four-necked flask containing 120 mL of deionized water, and 5-30 mg of citric acid was added. Under continuous stirring, the mixed alkali solution was added dropwise. When the pH of the solution was 10 ± 0.1, the addition of the alkali solution was stopped. After stabilization for 5-10 minutes, 100 mL of mixed salt and mixed alkali solution were added dropwise at the same time to keep the pH value of the solution stable at 10 ± 0.
1. After the addition of the mixed salt solution was completed, the obtained slurry containing the rGO / NF matrix was transferred to a reactor lined with polytetrafluoroethylene. Two pieces of 1.5 cm × 2.5 cm rGO / NF matrix and 75 mL of the above slurry were placed in each 100 mL reactor, and then crystallized at 80-120 ° C for 4-8 hours. After the reaction was completed, it was naturally cooled to room temperature. The obtained product was repeatedly washed with deionized water and freeze-dried for 5-8 hours to obtain a copper-based hydrotalcite / rGO / foam nickel hybrid precursor, denoted as M 2+ M 3+ -LDH / rGO / NF,M 2+ and M 3+ They are divalent and trivalent metal ions respectively; M in metal salt 2+ Cu 2+ or Cu 2+ with Ni 2+ 、Co 2+ , Mn 2+ and Mg 2+ A metal ion; (5) The product obtained in step (4) was placed in a flowing N2 of 50 to 200 mL / min, maintained at 380 to 600°C for 2 to 4 hours at a heating rate of 1 to 5°C / min, and then naturally cooled to room temperature to obtain a nanosheet array-type copper-based composite / rGO / nickel foam catalyst, denoted as Cu@Cu2O-M 2+ M 3+ (O) / rGO / NF.
3. The preparation method according to claim 2, characterized in that: The concentration range of the graphite oxide suspension described in step (3) is 0.5-3 mg / mL; the mass ratio of graphite oxide to citric acid is 2:1, and the ultrasonic power is 300W.
4. The preparation method according to claim 2, characterized in that: The mixed alkali in step (4) comprises NaOH and Na2CO3, and [CO3 2- ] / [M 3+ ]=2,[OH - ] / [CO3 2- ]=3.
2.
5. The preparation method according to claim 2, characterized in that: The mixed salt described in step (4) includes divalent and trivalent metal salts, which exist in the form of nitrate or acetate or a mixed form thereof, and the total molar number of the metal salt is 5 to 20 mmol, and M in the metal salt is 2+ Cu 2+ or Cu 2+ with Ni 2+ 、Co 2+ , Mn 2+ and Mg 2+ When M 2+ Cu 2+ When the trivalent metal ion M 3+ Fe 3+ and Al 3+ One or a combination of two of the above, with a molar ratio of M 2+ / M 3+ The value is 1.5~2, when M 3+ Fe 3+ and Al 3+ When the molar ratio of Fe 3+ / Al 3+ The value is 1 / 9~1; when M 2+ Cu 2+ with Ni 2+ 、Co 2+ , Mn 2+ and Mg 2+ When one of the 3+ Only Al 3+ , molar ratio M 2+ / M 3+ The value is 3 / 1, then Cu 2+ The molar number is 0.625~10mmol.
Citation Information
Patent Citations
Graphene-oriented multi-level structure composite oxide catalyst and preparation method thereof
CN104857960A
Preparation method and application of cuprous-oxide-loaded-on-foam-nickel composite graphene oxide photocatalyst
CN107413345A
Honeycomb nanosheet array nickel cobaltate / rGO / foamed nickel and preparation method thereof
CN110189922A